Using of Laser Therapy in the Treatment of Patients With Plantar Fasciitis - Jaddue, Dhia AK; Al-dulaimi, Ali. Sulaiman. M. Said (AL-Kindy College Medical Journal, 2008)
Background: planter fasciitis is a common condition seen in adults and sport men, it is characterized by dull pain in the heel, especially when getting up and standing on the foot in the morning or after sitting for a long time. Recently low level laser therapy is used as a method of treatment. Objective: to evaluate the benefit of laser therapy in treatment of planter fasciitis. Methods: Out of twenty five patients with planter fasciitis exposed to laser therapy. Laser used is (diode type) given in two cessions per week for four weeks, time for each cession is about (12 minutes). Results: complete recovery seen in (32%) of patients, moderate improvement in (16%), mild improvement in (24%), no response in (28%), deterioration (0%). Conclusion: laser therapy is safe for treatment of planter fasciitis, free of side effects, very effective as an alternative to surgery and local steroid injection, with no deterioration in the condition during or after laser therapy